Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

The first toxicological assessment of copper exposure in Cipangopaludina cathayensis: Integrative insights from gut microbiota and hepatopancreas responses - Linli Li; Jinyou Wei; Yufan Deng; Jing Yu; Xiayun Wei; Weiying Wang; Jiamin Chen; Jing Wei; Tiantian Yuan; Haizhen Tan; Zhengjun Wu; Jiaoyun Jiang (Environmental Pollution, 2026)

Correction: Testing the validity of the Montgomery–Koyama–Smith equation and the power law equation using 3231 tepals of a Magnolia species - Linli Deng; Jinfeng Wang; Li Zhang; Dirk Hölscher; Peijian Shi (Trees, 2025)

Testing the validity of the Montgomery–Koyama–Smith equation and the power law equation using 3231 tepals of a Magnolia species - Linli Deng; Jinfeng Wang; Li Zhang; Dirk Hölscher; Peijian Shi (Trees, 2025)
Key message The power-law equation provides marginally better accuracy than the Montgomery–Koyama–Smith equation for estimating total tepal area, with flexible definitions of maximum tepal length maintaining prediction reliability. Abstract Montgomery–Koyama–Smith equation (MKSE) and power law equation (PLE) were evaluated for estimating the total tepal area ( A T ) of Magnolia × soulangeana flowers using 3231 tepals from 359 flowers. MKSE assumes an isometric relationship between the A T and the product of summed tepal widths ( L KS ) and maximum tepal length ( W KS ), while PLE incorporates an allometric scaling exponent (α). Results showed α = 0.9561 (95% CI 0.9481–0.9641), confirming allometry. PLE exhibited slightly lower root-mean-square error (RMSE: 0.0149 vs. 0.0172) and mean absolute percentage error (MAPE: 1.18% vs. 1.35%) than MKSE. Redefining W KS as a random selection from the largest 9, 6, or 3 tepal lengths per flower minimally affected model performance, with MAPE consistently below 5% even when sampling the entire length range. This flexibility simplifies field measurements without compromising accuracy. Variability in geometric series common ratios across flowers likely drives the observed allometric scaling. This study validates that A T can be reliably estimated using summed widths and a flexibly defined maximum length, emphasizing PLE’s marginally superior fit. These findings advance methods for non-destructive floral trait quantification in species with fixed organ counts.

Alterations in glucose metabolism and shikimate pathway affected by transient overexpression of CsPAL gene in postharvest citrus fruit - Linli Wei; Wenjun Wang; Xiaoquan Gao; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Citrus transcription factor CsERF098 cooperates with CsWRKY70 to participate in response of fruit to green mold - Ting Li; Wenjun Wang; Qi Chen; Ou Chen; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Transcription factor CsERF1B regulates postharvest citrus fruit resistance to Penicillium digitatum - Ting Li; Wenjun Wang; Qi Chen; Jialin Chen; Xuan Zhang; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Genome-wide identification of the CsPAL gene family and functional analysis for strengthening green mold resistance in citrus fruit - Linli Wei; Wenjun Wang; Ting Li; Ou Chen; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Effects of dietary cholesterol supplementation on growth and cholesterol metabolism of rainbow trout (Oncorhynchus mykiss) fed diets with cottonseed meal or rapeseed meal - Junming Deng; Xi Zhang; Xiaowen Long; Linli Tao; Zhen Wang; Guoyi Niu; Bin Kang (Fish Physiology and Biochemistry, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Effect of ethanolic extract of propolis on growth performance and plasma biochemical parameters of rainbow trout (Oncorhynchus mykiss) - Junming Deng; Qingcong An; Baoliang Bi; Qiuju Wang; Lingfu Kong; Linli Tao; Xi Zhang (Fish Physiology and Biochemistry, 2011)

Detection of Bifidobacterium Species-specific 16S rDNA Based on QD FRET Bioprobe - JunFeng Jiang; ZhiHui Peng; Le Deng; Guang Li; LinLi Chen (Journal of Fluorescence, 2010)